Suture line ulcer due to use of non-absorbable material in gastric surgery: about 4 observations - Badano Repetto, José L (Cirugía del Uruguay, 1975)
Four cases of this ailment are presented, 3 of them following pyloroplasties -without vagotomy- due to pyloric hypertrophy, and the other one performed after distal gastric resection for ulcer, Billroth II type. They became evident through pain, and one of them a third ene was solved by vagotomy and a new pyloroplasty (Finney), and on the patient who had already been gastrectomized it was solved by excision of the suture thread by gastrostomy. Histopathology showed foreign body granulomas centered in the suture and ulcered in the mucous lining. The pathogenesis of this lesion is discussed.